The Right to Identity in the Convention on the Rights of the Child, 1989 - Omarova, Aisel (Український політико-правовий дискурс, 2026)
The UN Convention on the Rights of the Child 1989 (CRC) is the first international instrument to enshrine the child’s right to identity. And this is no coincidence. It was preceded by events in Argentina, specifically the period of the military junta’s ‘Dirty War’ between 1974 and 1983. During this time, the military regime altered children’s identities, which led the Argentine delegation to propose including the right to identity alongside other children’s rights in the text of the draft Convention. The discussion of the article on the right to identity lasted two years and reflected the dynamics of the debate surrounding the right to identity, as well as what the drafters understood by the very concept of the right to identity. The very concept of identity is contained in two articles of the Convention on the Rights of the Child, namely Art.8 and Art.29(1)(c). This study examines the drafts of these articles proposed by the delegations of Argentina, Poland and Algeria. The article details the discussions, the proposals put forward by delegations, and the arguments regarding the inclusion or exclusion of specific words and phrases from the proposed draft articles; it also analyses the content of the child’s right to identity and identity as a component of the child’s right to education. The methodological basis of the article consists of historical-legal and comparative-legal methods, which made it possible to trace the debates regarding key words and phrases in the draft article on the right to identity. The selection of sources was based on the principles of representativeness and reliability, drawing on the text of the Convention on the Rights of the Child, materials from meetings of the drafting committee, and sessions of the UN Human Rights Commission. The results of the analysis of drafts and proposals regarding the article on the right to identity reveal differences in how various delegations perceive the concept of the right to identity and the importance of its various aspects. The study concludes that it was only after the inclusion of an article on the right to identity in the text of the CRC that a change to a child’s identity came to be recognised as a violation of the child’s rights at the international level.